Using Top-Ranking Sentences to Facilitate Effective Information Access - White, Ryen W.; Jose, Joemon M.; Ruthven, Ian (Journal of the American Society for Information Science and Technology (JASIST), 2005)
Web searchers typically fail to view search results beyond the first page nor fully examine those results presented to them. In this article we describe an approach that encourages a deeper examination of the contents of the document set retrieved in response to a searcher’s query. The approach shifts the focus of perusal and interaction away from potentially uninformative document surrogates (such as titles, sentence fragments and URLs) to actual document content, and uses this content to drive the information seeking process. Current search interfaces assume searchers examine results document-by-document. In contrast our approach extracts, ranks and presents the contents of the top-ranked document set. We use query-relevant top-ranking sentences extracted from the top documents at retrieval time as fine-grained representations of top-ranked document content and, when combined in a ranked list, an overview of these documents. The interaction of the searcher provides implicit evidence that is used to reorder the sentences where appropriate. We evaluate our approach in three separate user studies, each applying these sentences in a different way. The findings of these studies show that top-ranking sentences can facilitate effective information access.